Some guidelines on the transition from the old horse to the new table - Sands, A.; McNeal, J. R. (2002)
The new vault table (NT) has been adopted by the International Gymnastics Federation (FIG) and is slowly being adopted by all countries and all levels of gymnastics. The U.S. elite program was the first to work with the NT due to the need to prepare for the Ghent World Championships in late 2001. The rapid implementation of the NT by the FIG has resulted in some necessary adaptations to vaulting and our approach to training of vaulting. As the NT is adopted by the J.O. program, it will be important for coaches to study the NT and identify possible modifications of training and thinking with regard to the NT dimensions.